3d+7=3(d-3)

Simple and best practice solution for 3d+7=3(d-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3d+7=3(d-3) equation:


Simplifying
3d + 7 = 3(d + -3)

Reorder the terms:
7 + 3d = 3(d + -3)

Reorder the terms:
7 + 3d = 3(-3 + d)
7 + 3d = (-3 * 3 + d * 3)
7 + 3d = (-9 + 3d)

Add '-3d' to each side of the equation.
7 + 3d + -3d = -9 + 3d + -3d

Combine like terms: 3d + -3d = 0
7 + 0 = -9 + 3d + -3d
7 = -9 + 3d + -3d

Combine like terms: 3d + -3d = 0
7 = -9 + 0
7 = -9

Solving
7 = -9

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 8=-4/7n | | 7x-4=4y | | 3r(2r+1)=21 | | N^2+-18N+17=0 | | 3log(x-5)=log(35-x^3) | | 4z/3-=2z | | 3(4x-1)(4x+3)=49x | | Y(n)=4.5n-8 | | -6r+10=-10+4r | | 49=-7/9x | | 3ln(x-5)=ln(35-x^3) | | 4x+2+6x+8=30 | | 1/9/5.40 | | 42=-(x-4) | | -8-4n=-3n | | 30+4x+2+6x+8= | | 1.4y+2.2=0 | | 10=3u+1 | | -4(x-12)-2=6 | | 3y-2+2y+7-y= | | 8x^2+5=12x | | x+g=21 | | 4(-2y+3)= | | 119+9-3a=-7 | | 5x-1x+3=5 | | 8x-4=15x-18 | | 8=-7+y | | 10b^3+4b^2= | | 3-6b+13=26 | | Z^2+-9Z+18=0 | | Logs=0.06 | | 1520=38(p+10) |

Equations solver categories